Polarization-insensitive composite gradient-index metasurface array for microwave power reception - Yang, Qiang; Xiong, Han; Deng, Jia-Hao; Wang, Ben-Xin; Peng, Wen-Xiong; Zhang, Huai-Qing (Applied physics letters, 2023)
A composite gradient-index metasurface (C-GM) array for microwave power reception (MPR) operating at 5.8 GHz center frequency was introduced. The array is insensitive to the polarization of incident plane waves and possesses cosine gradient modulation characteristics, which can convert the incident plane waves into surface waves focused at the center of the array. The focused surface wave energy is then collected by an omnidirectional antenna and fed back to a single rectifier for radio frequency (RF) to direct current (DC) conversion, resulting in DC output. Simulation results show that the array can fully excite surface waves under different polarized plane wave excitations, and the omnidirectional antenna has good matching characteristics with the array, achieving an energy collection efficiency of 66.52%. The array was fabricated and measured, achieving an energy reception efficiency of 59.91% and an RF-DC conversion efficiency of 34.83%, which is consistent with the simulation results. The proposed C-GM array can capture higher electromagnetic power by simply increasing its size, without the need for additional rectifiers or complex matching networks, making it a flexible and efficient MPR solution for different application scenarios.